PATOMEKANISME HILANG PENGLIHATAN IATROGENIK AKIBAT PROSEDUR FILLER WAJAH - Nabila Maudy Salma; Lenny Setiawati; Dian Mediana; Deasyka Yastani; Keilani Prigel Salma (Jurnal Akta Trimedika, 2025)
Currently, the use of dermal fillers on the face is increasing, as evidenced by the rising life expectancy, leading many people to seek solutions for early aging. This procedure aims to minimize facial wrinkles and enhance skin volume through the injection of substances such as hyaluronic acid or autologous fat. Although this procedure is generally considered safe with a low risk of complications, there are possibilities of serious complications, such as blindness, stroke, or even death, caused by arterial occlusion. Vision loss due to facial filler injections is a rare occurrence, first reported more than 50 years ago. This case is typically related to occlusion of small blood vessels in the facial area, such as branches of the ophthalmic artery that anastomose with other arteries. The main mechanism of vision loss is retrograde embolism that blocks blood flow to the retina, causing ischemia and blindness. Some facial areas at high risk for these complications include the glabella, nasolabial area, and frontal region. Other factors that may exacerbate this condition include high injection pressure, which can affect arterial blood flow and increase the likelihood of occlusion. Understanding the pathomechanism is important to reduce the risk of complications in facial filler procedures and to provide education to both patients and medical professionals to perform this procedure safely